Pengaruh Konseling Kelompok Teknik Wdep Terhadap Penurunan Prokrastinasi Akademik Siswa Kelas Xi Smk Negeri Rowokangkung - Bunga Salsa Anindya; Muhammad Fikri Fauzi; Faisol Hakim (CV. SINAR HOWUHOWU, 2026)
In today's rapidly developing era, students are required to possess competencies, skills, discipline, and innovation abilities. However, many students still experience various academic problems, one of which is academic procrastination. Therefore, efforts are needed to help students reduce such behavior. This study aimed to determine the effect of group counseling using the WDEP (Wants, Doing, Evaluation, Planning) technique on reducing students' academic procrastination. This study employed a quantitative approach with a quasi-experimental design. The sample consisted of 16 students with high levels of academic procrastination selected through purposive sampling. Data were analyzed using the Independent Samples t-Test. The results showed a significant difference in the mean scores between the control group and the experimental group, namely 64.5000 and 78.6250, respectively, after the implementation of group counseling with the WDEP technique. This finding indicates that group counseling using the WDEP technique is effective in reducing students' academic procrastination. Therefore, the WDEP technique can be used as an effective guidance and counseling service to help decrease academic procrastination among students.